ALAT PENDETEKSI NOMINAL DAN KEASLIAN MATA UANG KERTAS - Rakhmad Kuswandhie (LPPM UNIVERSITAS BINA INSAN, 2015)
In the conventional process of buying and selling there will be a meeting between several people who act as sellers and buyers. But with current technology developments then the process of buying and selling can also be done without a direct meeting between the seller da. Besides buying and selling process also is not always the case between man and man, but already possible to do with an intermediary tool.Tools used in this transaction should be able to detect the nominal and the authenticity of money to support the process of buying and selling. For that to know the characteristics and traits of each currency. In addition to the tool can work automatically then need to be prepared several electronic circuits which include optocoupler circuits and other support circuits. As for the introduction of nominal and authenticity of the money it can use image capture devices such as cameras and then that image will be processed with the help of software that will detect the nominal value and authenticity of banknotes.With a combination of software and hardware is expected to generate a nominal detection tools and authenticity of paper money that can work automatically with the computer base